Crop rotation with crotalaria ochroleuca and urochloa ruziziensis for the management of plant-parasitic nematodes in sugarcane - Leila Luci Dinardo-Miranda; da Silva, Higor Domingos Silvério; Dinardo-Miranda, Giulia (REVISTA DE AGRICULTURA, 2026)
Plant-parasitic nematodes cause extensive damage each year to sugarcane crops in Brazil. Since it is almost impossible to eradicate nematodes in a field, several practices must be used to manage an infested area, including growing cover crops between sugarcane cycles. This study aimed to determine the effects of Crotalaria ochroleuca and Urochloa ruziziensis during sugarcane renewal field on the nematode population in subsequent sugarcane roots and soil. Growing C. ochroleuca between sugarcane cycles contributes to reducing populations of Meloidogyne incognita and a mixed population of Pratylenchus zeae and P. brachyurus in sugarcane roots and soil at least throughout the first two months after planting. On the other hand, growing U. ruziziensis between two sugarcane cycles does not affect the M. incognita and P. zeae populations in sugarcane roots.